The Program of Circuit Isbat Nikah as the Embodiment of Access to Justice in Indonesia (UINSI Samarinda, 2018)
Human rights guaranteed by the Constitution require, among other things, that every citizen should be able to access the judiciary. In reality, however, not all citizens can access the judiciary in Indonesia due to various factors including litigation costs, ignorance of litigation procedures, and distance problem. The same situation is also experienced by the society seeking for justice through Islamic judiciary (Pengadilan Agama or PA) across Indonesia. One of the Religious Courts deserved for a case study is PA Tenggarong. PA Tenggarong is one of the Religious Courts in East Kalimantan, which covers two district areas, namely Kutai Barat and Kutai Kartanegara. Kutai Barat consists of 12 sub-districts with 182 villages, while Kutai Kartanegara has 18 sub-districts with 227 villages. The geographical conditions and locations of the villages are mostly far away from the PA Tenggarong that render it difficult for the justice seekers in accessing the court, and, thus, obtaining their rights. Their legal problems mainly come from their unregistered marriages which make their unions do not exist according to the effective law. Hence, this article analyzes how the program of the legalization of unregistered marriages (isbat nikah) in PA Tenggarong has been implemented in order to assist the justice seekers in securing the legal certainty of marriage status. The finding reveals that the process of the legalization of marriage is conducted as a circuit marriage contract in different sub-district/village office or decent premises across Kutai Barat and Kutai Kartanegara. The program is free for eligible parties and is facilitative towards their needs and conditions, namely lacks of legal documents, ignorance of the litigation procedures, and afar domicile. This thus makes PA Tenggarong now more accessible to the public and the circuit isbat nikah as the embodiment of access to justice principle in Indonesia.Keywords:Circuit isbat nikah, access to justice, Islamic Judiciary in Indonesia